The social representation of aggression among student groups in UP Diliman an exploratory study - Puyat, Joseph H. (2000)
Majority of the psychological studies conducted on aggression focused on the neurobiological and situational determinants of aggressive behavior. Recently, basic cognitive processes were investigated and found to be significantly predictive of aggressive behavior. In many of these studies, however, cognitive processes were almost always treated as an individual phenomenon; virtually immune to the influences of group membership. A different stance was taken in this study. Here, cognitive processes were presumed to be frequently subject to the influences of group-shared knwoledge structures. By studyung the elements and structure of these shared cognitions, a better understanding of how individuals process information that influence their aggressive actions would be gained. This exploratory study was carried out with this objective in mind. Group based on gender and membership in fraternities/sororities were used for comparison. To determine the elements of shared cognitions, respondents were asked to write down everything that comes to their mind when they hear or see the word aggression. The data collected from this world association task were subjected to correspondence analysis to determine how the elements were structured. Results revealed that respondents' thoughts were organized using the individual-intergroup and abstract-concrete dimensions. Other aspects of the representation, such as the centrality of intention, the instrumentality dimension, and achoring in past expereinces and valye priorities were investigated using survey questionnaires. Results of the analysis inidcated that most respondents tend to give less importance to intention as an esential element defining aggressive acts. The negative consequence of aggression, in the form of emotional to physical harm, appeared to be most salient to the majority of respondents. Men, in general, and fraternity members in particular, subscribed to a more instrumental representation of aggression. This orientation towards aggression was alos found to be positively correlated with the number of years a fraternity man has been a member of his organization, implying further that most fraternities nurtured this type of representation. Finally, the instrumental representation of aggressive was found to be positively correlated with values represnting power and hedonism and negatively correlated with values such as benevolence, universalism, tradition and conformity. Men, in this sample, scored higher on the benevolence, universalism, tradition and conformity values. This observed link between the instrumental representation and certain value types was discussed in light of the current literature on the subject.
Thesis (M.A. Psychology)--University of the Philippines Diliman.
Vita.
"March 2000."
Research project funded by the University through the Office of the Vice-Chancellor for Research and Development (OVCRD).
Keywords: Aggressiveness(Psychology)in youth -- Philippines -- Quezon City; College students -- Social conditions. -- Philippines